Genome-Wide Analysis of the FNSII Gene Family and the Role of CitFNSII-1 in Flavonoid Synthesis in Citrus - Xinya Liu; Beibei Chen; Ling Luo; Qi Zhong; Chee How Teo; Shengjia Huang (Plants)
Flavonoid synthases (FNSs) are key enzymes catalyzing the conversion of flavanones to flavonoids, yet their functions in citrus remain functionally uncharacterized. In this study, we identified three FNSII genes in the citrus genome. Phylogenetic analysis revealed that citrus FNSII genes share the closest evolutionary distance with apple FNSII genes. Chromosomal localization demonstrated that the three FNSII genes are distributed across two out of nine chromosomes. Gene structure analysis indicated that the majority of motifs within these three FNSII genes are highly conserved. We cloned a gene called CitFNSII-1 from citrus. Transient overexpression of CitFNSII-1 in citrus leaves significantly increased flavonoid content, while simultaneous virus-induced silencing of CitFNSII-1 led to synchronously and significantly reduced gene expression levels and flavonoid content in citrus seedlings. Through the Agrobacterium rhizogenes-mediated genetic transformation system, overexpression of CitFNSII-1 was found to markedly enhance flavonoid accumulation in hairy roots, whereas knockout of CitFNSII-1 resulted in a significant decrease in flavonoid content in hairy roots. Further experiments verified an interaction between CitFNSII-1 and the Chalcone isomerase-1 (CHI-1) protein. The results demonstrated that the flavonoid accumulation patterns of CHI-1 and CitFNSII-1 are highly similar. In conclusion, this study advances the understanding of the flavonoid biosynthesis pathway in citrus and provides a theoretical foundation for molecular breeding strategies in citrus.